Build-ups in the supply chain of the brain: on the neuroenergetic cause of obesity and type 2 diabetes mellitus - Peters, Achim; Langemann, Dirk (Frontiers in Neuroenergetics, 2009)
Obesity and type 2 diabetes have become the major health problems in many industrialized countries. A few theoretical frameworks have been set up to derive the possible determinative cause of obesity. One concept views that food availability determines food intake, i.e. that obesity is the result of an external energy “push” into the body. Another one views that the energy milieu within the human organism determines food intake, i.e. that obesity is due to an excessive “pull” from inside the organism. Here we present the unconventional concept that a healthy organism is maintained by a „competent brain-pull“ which serves systemic homeostasis, and that the underlying cause of obesity is “incompetent brain-pull”, i.e. that the brain is unable to properly demand glucose from the body. We describe the energy fluxes from the environment, through the body, towards the brain with a mathematical “supply chain” model and test whether its predictions fit medical and experimental data sets from our and other research groups. In this way, we show data-based support of our hypothesis, which states that under conditions of food abundance incompetent brain-pull will lead to build-ups in the supply chain culminating in obesity and type 2 diabetes. In the same way, we demonstrate support of the related hypothesis, which states that under conditions of food deprivation a competent brain-pull mechanism is indispensable for the continuance of the brain´s high energy level. In conclusion, we took the viewpoint of integrative physiology and provided evidence for the necessity of brain-pull mechanisms for the benefit of health. Along these lines, our work supports recent molecular findings from the field of neuroenergetics and continues the work on the “Selfish Brain” theory dealing with the maintenance of the cerebral and peripheral energy homeostasis.